Odpowiedzi

2010-02-28T18:22:40+01:00
A)a+(a-b)=a+a-b=2a-b
b)2x-(x+4)=2x-x+-4=x-4
c)7-(-x+6)=7+x-6=x+1
d)-(x+4)+(x-5)=-x-4+x-5=-9
e)1-(t+p)-(t-2)=1-t-p-t+2=-2t-p+3
f)-(-y+2)+(-2y-4)=y-2-2y-4=-y-6
2010-02-28T18:23:31+01:00
A)a+(a-b) = 2a - b
b)2x-(x+4) = x + 4
c)7-(-x+6) = x + 1
d)-(x+4)+(x-5) = -x - 4 + x - 5 = -9
e)1-(t+p)-(t-2) = 1 - t - p - t + 2 = -2t - p +3
f)-(-y+2)+(-2y-4) = y - 2 -2y - 4 = -y - 6
2010-02-28T18:24:30+01:00
A)2a-b
b)x-4
c)7+x-6=x+1
d)x-4+x-5=-9
e)1-t-p-t+2=3-2t-p
f)y-2-2y-4=-y-6